Essays in corporate finance - Park, NY (2013)
Prior research on corporations finds that there exists a large unexplained firm-specific heterogeneity in corporate behaviors stemming from the effects of managers. This research identifies managerial personalities and tests their effects on corporate behaviors both experimentally and empirically. First, the effects of managerial personalities on corporate financing decisions are tested using a laboratory experiment with managers in South Korea. The laboratory experimental market is à la Modigliani and Miller but with two frictions, bankruptcy costs and corporate taxation. Leverage choices of managers with particular personality traits are compared against the optimal capital structure computed from the static trade-off theory. The results show that extravert managers choose higher leverage ratios, with the effect being financially meaningful although not statistically significant. Secondly, I identify extravert CEOs and empirically measure its effects on corporate financing choices using Chief Executive Officers’ avocation data and corporate financial data of public, nonfinancial US companies between 1992 and 2011. The results of mean comparisons by group, fixed effects regressions, difference-in-difference regressions, and changes of leverages around CEO turnovers show that extravert CEOs tend to issue risky debt more when accessing external finance and maintain higher leverage ratios than their peers. Thirdly, I test the effects of managerial extraversion on executive compensation. I first offer an empirical compensation model of managerial bargaining power, and then empirically tests the prediction by identifying a personality trait relevant to bargaining power using a novel set of managerial hobbies data. The results provide an evidence that CEO bargaining power has an increasing effect on CEO compensation.